How to tell the time: the regulation of phosphoenolpyruvate carboxylase in Crassulacean acid metabolism (CAM) plants. (1st June 2003) - Nimmo, H.G.
Abstract : Crassulacean acid metabolism (CAM) plants exhibit persistent circadian rhythms of CO2 metabolism. These rhythms are driven by changes in the flux through phosphoenolpyruvate carboxylase, which is regulated by reversible phosphorylation in response to a circadian oscillator. This article reviews progress in our understanding of the circadian expression of phosphoenolpyruvate carboxylase kinase.